Solitary Fibrous Tumor of the Retroperitoneal Space. (9th January 2021) - Marcinek, Mateusz; Majcherczyk, Konrad; Nowak, Marcel; Targoński, Aleksander; Tkocz, Michał
Abstract : A solitary fibrous tumor develops from mesenchymal cells as a pleural neoplasm, but it is also occasionally reported in extrapleural sites. Retroperitoneal tumors are a group of neoplasms located between muscles and the fascia of the posterior abdominal wall and the parietal peritoneum. Their cytology differs from that of urinary tract organs or adrenals. This case report presents a rare solitary fibrous tumor incidentally found during an ultrasound examination. A 54-year-old male underwent urgent surgery for a tumor located in the left retroperitoneal space. The histologic examination confirmed a solitary fibrous tumor with a 5% Ki67 proliferation index, a 1 MF/10 HPF mitotic activity, and CD34-positive immunostains. A solitary fibrous tumor is a rare retroperitoneal tumor. Its symptoms and signs might resemble those of the classical triad of renal cell carcinoma, although the tumor's growth phase is typically asymptomatic. Intraoperative diagnosis of a solitary fibrous tumor strongly recommends radical excision.